Ameliorating Role Exerted by Al-Hijamah in Autoimmune Diseases: Effect on Serum Autoantibodies and Inflammatory Mediators - Baghdadi, Hussam; Abdel-Aziz, Nada; Ahmed, Nagwa Sayed; Mahmoud, Hany Salah; Barghash, Ayman; Nasrat, Abdullah; Nabo, Manal Mohamed Helmy; El Sayed, Salah Mohamed (International Journal of Health Sciences, 2015)
Autoimmune diseases have common properties characterized by abnormal blood chemistry with high serum autoimmune antibodies, and inflammatory mediators. Those causative pathological substances (CPS) cannot be excreted by physiological mechanisms. Current treatments for autoimmune diseases involve steroids, cytotoxic drugs, plasmapheresis and monoclonal antibodies. Wet cupping therapy (WCT) of prophetic medicine is called Al-hijamah that treats numerous diseases having different etiology and pathogenesis via a pressure-dependent and size-dependent non-specific filtration then excretion of CPS causing clearance of blood and interstitial fluids. Al-hijamah clears blood passing through the fenestrated skin capillaries. Medical bases of Al-hijamah were reported in the evidence-based Taibah mechanism (Taibah theory). Al-hijamah was reported to be an excellent treatment for rheumatoid arthritis that improved patients’ blood chemistry and induced significant clinical improvement and pharmacological potentiation. Al-hijamah improved the natural immunity and suppressed the pathological immunity through decreasing the serum level of autoantibodies, inflammatory mediators, and serum ferritin (a key player in autoimmunity). Al-hijamah reduced significantly pain severity, number of swollen joints and disease activity with no significant side effects. Main steps of Al-hijamah are skin suction (cupping), scarification (sharat mihjam in Arabic) and second suction (triple S technique) that is better therapeutically than the traditional WCT (double S technique). Whenever an excess noxious substance is to be removed from patients' blood and interstitial fluids, Al-hijamah is indicated. Shartat mihjam is a curative treatment in prophetic teachings according to the prophetic hadeeth: "Cure is in three: in shartat mihjam, oral honey and cauterization. I do not recommend my nation to cauterize". Al-hijamah may have better therapeutic benefits than plasmapheresis. Al-hijamah may be promising in treating autoimmune diseases as a sole treatment or adjuvant treatment. Key words: Autoimmune diseases, Al-hijamah, Prophetic medicine, Serum ferritin, Rheumatoid arthritis and Plasmapheresis.